Analisis Akurasi Sistem sensor DHT22 berbasis Arduino terhadap Thermohygrometer Standar: Fitri Puspasari, Trias Prima Satya, Unan Yusmaniar Oktiawati, Imam Fahrurrozi, Hristina Prisyanti - Fitri Puspasari Fitri Puspasari; Trias Prima Satya Trias Prima Satya; Unan Yusmaniar Oktiawati Unan Yusmaniar Oktiawati; Imam Fahrurrozi Imam Fahrurrozi; Hristina Prisyanti Hristina Prisyanti (Jurnal Fisika dan Aplikasinya, 2020)
The research of temperature and humidity comparison test using DHT22 sensor instrument based on Arduino Uno by Thermohigrometer. The background of this research problem is the development of increasingly advanced technology to facilitate measurement of temperature and humidity using DHT22 sensor based on Arduino. The aims of this tesearch was to knowing the sensor performance and comparing measurement result between DHT 22 sensor and standard thermohygrometer. The experiment was done using 5 times repeatability method at each room temperature variation. Comparison of the results of the average error value in the measurement of temperature and humidity between the DHT22 sensor with a standard Thermohygrometer obtained a value of 2.99% for humidity and -2.31% for temperature.